2017
DOI: 10.1186/s12913-017-1984-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations between degrees of task delegation and job satisfaction of general practitioners and their staff: a cross-sectional study

Abstract: BackgroundIn recent years, the healthcare system in the western world has undergone a structural development caused by changes in demography and pattern of disease. In order to maintain the healthcare system cost-effective, new tasks are placed in general practice urging the general practitioners to rethink the working structure without compromising the quality of care. However, there is a substantial variation in the degree to which general practitioners delegate tasks to their staff, and it is not known how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
6
11
0
Order By: Relevance
“…A previous study on the association between degrees of task delegation and satisfaction of GPs found that greater clinical staff member involvement was associated with increased job satisfaction of GPs [22]. In line with this current study, GPs applied a great variation in the degree of task delegation in clinics [22].…”
Section: Strengths and Weaknesses In Relation To Other Studiessupporting
confidence: 87%
See 2 more Smart Citations
“…A previous study on the association between degrees of task delegation and satisfaction of GPs found that greater clinical staff member involvement was associated with increased job satisfaction of GPs [22]. In line with this current study, GPs applied a great variation in the degree of task delegation in clinics [22].…”
Section: Strengths and Weaknesses In Relation To Other Studiessupporting
confidence: 87%
“…A previous study on the association between degrees of task delegation and satisfaction of GPs found that greater clinical staff member involvement was associated with increased job satisfaction of GPs [22]. In line with this current study, GPs applied a great variation in the degree of task delegation in clinics [22]. The more positive responses to task delegation in the previous study can be explained by their use of chronic obstructive pulmonary disease as the condition [22].…”
Section: Strengths and Weaknesses In Relation To Other Studiessupporting
confidence: 84%
See 1 more Smart Citation
“…Additionally, the question surveying job satisfaction was further tested in a recent survey on GPs’ job satisfaction in relation to task delegation. 13 Data on responders versus non-responders to the questionnaire are shown elsewhere. 11…”
Section: Methodsmentioning
confidence: 99%
“…Seen from a working environmental perspective, recent research has found that a high degree of task delegation is associated with a high degree of job satisfaction among the staff and that there is a tendency of a similar pattern in the case of GPs [5]. Job satisfaction is found to be associated with good quality care and is therefore important to the patients’ care as well.…”
mentioning
confidence: 99%